Korelasi Persepsi Kemampuan Metakognitif dan Kemampuan Berpikir Kritis Siswa selama Pandemi Covid-19 di SMA Unggulan Nurul Islami Mijen - Ayu Cendana, Chinta Celi; Harjono, Harjono; Haryani, Sri; Nuswowati, Murbangun (Universitas Negeri Semarang, 2021)
One that students need in the 2013 curriculum is metacognitive abilities. Some research results show that metacognitive abilities affect critical thinking skills. Researchers are interested in explaining the relationship between metacognitive abilities and critical thinking abilities. The purpose of this study was to determine the correlation between the perception of metacognitive abilities and the critical thinking skills of XI grade high school students at SMA Ungulan Nurul Islami Mijen during the Covid-19 pandemic. The sample used was 30 students from class XI MIPA Superior High School Nurul Islami Mijen. The research data were obtained using questionnaires and tests. The results of the analysis using the PLS technique show that there are three models that have been successfully obtained, namely model 1 as the initial model, model 2 estimation from model 1 and model 3 as the final model. Based on the justification of the analysis, model 3 is considered the best research model. In this study, it can be concluded that there is a correlation between the perception of metacognitive abilities on the critical thinking skills of Grade XI high school students at SMA Unggul Nurul Islami Mijen during the Covid-19 pandemic of 0.360.